2016
DOI: 10.1021/acsami.6b00158
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticle Modified Scaffold Interface Enhances Vascularization of Bone Grafts by Activating Calcium Channel of Mesenchymal Stem Cells

Abstract: Insufficient blood perfusion is one of the critical problems that hamper the clinical application of tissue engineering bone (TEB). Current methods for improving blood vessel distribution in TEB mainly rely on delivering exogenous angiogenic factors to promote the proliferation, migration, differentiation, and vessel formation of endothelial cells (ECs) and/or endothelial progenitor cells (EPCs). However, obstacles including limited activity preservation, difficulty in controlled release, and high cost obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 48 publications
2
64
0
Order By: Relevance
“…However, little originally implanted material decomposition was detected in scaffold at the same time point. These results confirmed that the increased penetration of blood vessel was very useful for the formation of new bone tissue inside of TEB [54]. Among biomaterials, bioactive glasses were widely used in bone defect reparation because they spontaneously bonded and integrated with both soft and hard (bone) tissues in living body.…”
Section: Tissue Engineeringsupporting
confidence: 70%
See 1 more Smart Citation
“…However, little originally implanted material decomposition was detected in scaffold at the same time point. These results confirmed that the increased penetration of blood vessel was very useful for the formation of new bone tissue inside of TEB [54]. Among biomaterials, bioactive glasses were widely used in bone defect reparation because they spontaneously bonded and integrated with both soft and hard (bone) tissues in living body.…”
Section: Tissue Engineeringsupporting
confidence: 70%
“…In order to isolate the influence of Ce valance states of CNPs on cell proliferation, Human Mesenchymal Stem Cells (HMSCs) and osteoblast-like cells (MG63) were cultured on the PL/CNP surfaces with dominant Ce 4+ and Ce 3+ regions. Tissue engineering bone (TEB) scaffold was modified with cerium oxide nanoparticles (CNPs) and the effects of CNPs existing at the scaffold surface on the growth and paracrine behavior of mesenchymal stem cells (MSCs) were investigated [54] (Figure 9(a)). MSCs were cultured on scaffold and scaffold@CNPs for 1, 7, and 14 days.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…The ability to scavenge superoxide related to cerium (III) concentrations at the surface particle [19]. On the other hand, SOD plays important role in redox biology and cellular Anti-inflammatory response [20]. Free radicals overproduction such as nitric oxide (NO) by the enzyme inducible nitric oxide synthase (iNOS) is critical to regulate inflammation.…”
Section: Cerium Oxide-based Nanomaterialsmentioning
confidence: 99%
“…Cerium oxide nanoparticles (CeONPs) have been regarded as a promising biomaterial for biomedical applications [43][44][45][46][47][48][49][50] due to their excellent properties. 51 Previous studies have shown that CeONPs are cytotoxic to cancer cells, inducing oxidative stress and causing lipid peroxidation and cell membrane leakage.…”
Section: Introductionmentioning
confidence: 99%